JESUS CHRIST’S IMAGE TRANSFORMATION IN THE WORKS BY A. BLOK: FROM EARLY WORKS TO THE POEM “THE TWELVE” - Grudinina, Elena Valeryevna (Neofilologiâ, 2018)
We present the analysis the image of Jesus Christ in the early lyric poetry and the final chapters of the poem “The Twelve” by A. Blok from the point of view of Orthodox spiritual thought. The study allows us to conclude that the poet, despite the specific creative manner of symbolism, very accurately conveys in his early works not only the crisis perception of the world, typical of society at the turn of the 19th and 20th centuries, but also a deep personal insight into the essence of Orthodox faith. As a result of comparing the image of Christ in the analyzed lyric works with the final image in the poem “The Twelve”, which received many different interpretations in critical literary practice, as well as the writings of philosophers and theologians, we conclude that Alexander Blok with his fine poetic ear and spiritual vision, astonishing accuracy portrayed the moral emptiness of people who had created an idol for themselves from a false idea. The element of destruction, the whirlwind of snow, which gave rise to the “tender” image of the false Christ, in fact poses a mortal danger to the human soul.